Monoclonal antibody neutralizes the sporozoite stage of different Theileria parva stocks - Dobbelaere, D.A.E.; Spooner, P.R.; Barry, W.C.; Irvin, A.D. (Wiley, 1984)
Summary Monoclonal antibodies were raised against sporozoites of Theileria parva. One of these antibodies (MAbDi) neutralized the infectivity of sporozoites for lymphocytes in vitro and for cattle in vivo. Neutralization seemed to occur by blocking sporozoite entry into the cell. MAbDi neutralized sporozoites of four unrelated stocks of T. parva, indicating the presence of a common antigenic determinant which may be important in initiating protective immunity.